Comparative analysis of modern theoretical approaches to sustainable economic development - V. V. Lebedev; A. E. Terpugov (Вестник университета)
The article provides a comparative assessment of domestic and foreign scientists’ and economists’ works, who studied theoretical approaches to sustainable economic development. Countries are increasingly integrating with each other, labor productivity is higher, but at the same time natural resources are used too intensively, which leads to environmental pollution. In this regard, it is necessary to pay more attention and even be unable to influence the processes aimed at ensuring stable economic growth. In the conditions of world economic relations transformation, economic systems activity sustainability is a key element of development and growth of national economies of states. The introduction and use of theoretical approaches in the process of studying the sustainable development of the economy makes it possible to systematize various properties of economic systems in the process of analyzing its development prospects. The obtained results of the conducted research can be used in theoretical frameworks evaluation aimed at studying the sustainable development of economy.